Anaerobic metabolism promotes breast cancer survival via Histone-3 Lysine-18 lactylation mediating PPARD axis - Ying Xu; Weiwei Meng; Yingqi Dai; Lin Xu; Ning Ding; Jinqing Zhang; Xuewei Zhuang (Cell Death Discovery)
Abstract Histone lactylation plays a crucial role in cancer progression, but its impact on breast cancer (BC) tumorigenesis is still unclear. We utilized chromatin immunoprecipitation sequencing with H3K18la antibodies, transcriptomics of clinical BC samples, and proteomics and ATAC-seq analyses of in vivo tumors to identify the genes regulated by H3K18la and the transcription factor PPARD. qPCR and Western blot assays were used to detect expressions of molecules. We discovered that H3K18la levels were higher in BC tissues compared to adjacent non-cancerous tissues. H3K18la promoted the expression of PPARD, which in turn influenced the transcription of AKT, but not ILK. ATAC-seq analysis revealed that glycolysis in BC cells enhanced chromatin accessibility. Additionally, we confirmed that HDAC2 and HDAC3 act as “erasers” for H3 lysine lactylation. During the proteomics analysis, AKT-phosphorylation in the aerobic respiration inhibitor group exhibited an apparent disparity and activity. Our study demonstrated that changes in H3K18la in BC and its downstream transcription factor PPARD support cell survival under anaerobic glycolysis conditions. PPARD accelerated cancer proliferation by promoting the transcription and phosphorylation of AKT. This highlights the therapeutic potential of targeting the H3K18la/PPARD/AKT axis in breast cancer, providing new insights into epigenetic regulation and cancer metabolism (Trial registration: The study was approved by the Research Ethics Committee Shandong Provincial Third Hospital (KYLL-2023057; https://www.medicalresearch.org.cn/ )).